Three Gorges Project: benefits and challenges for shipping development in the upper Yangtze River. Issue 5 (3rd September 2021) - Li, Wenjie; Wang, Dawei; Yang, Shengfa; Yang, Wei
ABSTRACT: The Three Gorges Project has benefited shipping development in the upper Yangtze River by improving the waterway channel and thus increasing ship load and port handling capacity. However, the Three Gorges lockage freight volume exceeded the designed capacity in 2011 (19 years sooner than expected), becoming a bottleneck for shipping development. For the predicted freight volume, building of a second ship lock with transit capacity of 150 million tons is suggested, and before it is built, ship organization should be optimized to increase transit capacity.